Continuous Auditing as a Strategic Tool in Public Sector Internal Audit: The Turkish Case - Rasim Sarıkaya; Sezer Bozkuş Kahyaoğlu; Bahadır Topal (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
In both public and private sectors, internal audit profession has become a fundamental requirement to improve business processes to achieve strategic goals. This is due to the fact that internal audit has a significant role with its value added risk-based approach and being trusted advisor in achieving strategic goals. Internal audit in public sector is a comparatively new practice in Turkey which became operative with the Public Financial Management and Control Law (No 5018) back in 2003 in order to ensure economic, efficient, effective utilization of public resources in line with the priorities and performance indicators of public administrations. After a short transition period, the public administrations have started to establish their internal audit functions with the full support of Internal Audit Coordination Board of Turkey based on IIA standards in such a tiny period of time. The major aim of this paper is to analyze the current state of public sector internal audit in Turkey and provide an example for the best practice. In this respect, internal audit function of the Turkish Ministry of Agriculture and Forest is chosen. This is because internal audit team of the Ministry uses a continuous auditing software which was developed in-house to conduct their audit plans, fieldworks and reports in digital. Firstly, the importance of continuous auditing and data analytics is explained based on relevant literature. Secondly, brief background information about the internal audit in Turkish public sector is given and internal audit function of the Ministry of Agriculture and Forestry is introduced shortly. Thirdly, the data, methodology and empirical results of the continuous auditing case of the Ministry is presented. In conclusion, policy recommendations are made based on empirical findings in order to contribute literature.